2010
DOI: 10.1016/j.freeradbiomed.2010.10.481
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and Oxidative Stress Status Following a Handball Game in Elite Male Players

Abstract: Background.Handball is considered an intermittent sport that places an important stress on a player's aerobic and anaerobic metabolism. However, the oxidative stress responses following a handball game remain unknown. We investigated the responses of plasma and erythrocyte antioxidant system and oxidative stress biomarkers following a single handball game. Methods. Fourteen male elite Brazilian handball athletes were recruited in the present study. Blood samples were taken before, immediately, and 24 hours aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…GSH plays a multifunctional role in protecting biomolecules from oxidative damage during exercise so the findings in this study may suggest an acute compensatory response of the antioxidant defenses against the ROS production. In agreement with this compensation theory, Marin et al (2011) found that GSH concentration was reduced immediately after a handball game. In addition to GSH/GSSG ratio, F2-Isoprostanes are considered to be the best available chemically stable biomarkers of oxidative stress induced lipid peroxidation in vivo (Roberts and Morrow 2000), that also present in detectable amounts in plasma and are unaffected by lipid content in the diet (Gopaul et al, 2000).…”
Section: Discussionsupporting
confidence: 70%
“…GSH plays a multifunctional role in protecting biomolecules from oxidative damage during exercise so the findings in this study may suggest an acute compensatory response of the antioxidant defenses against the ROS production. In agreement with this compensation theory, Marin et al (2011) found that GSH concentration was reduced immediately after a handball game. In addition to GSH/GSSG ratio, F2-Isoprostanes are considered to be the best available chemically stable biomarkers of oxidative stress induced lipid peroxidation in vivo (Roberts and Morrow 2000), that also present in detectable amounts in plasma and are unaffected by lipid content in the diet (Gopaul et al, 2000).…”
Section: Discussionsupporting
confidence: 70%
“…Stefanyk and Dyck (2010) et al showed that plasma TNF-α is generally unchanged by a single bout of exercise [11]. However, Marin et al (2011) showed that at plasma IL-6 levels increased significantly only immediately postgame and normalized at 24 hours in handball game in elite male players, the other unexpected result of their study was the significantly reduction of TNF-α after 24 hours of recovery [48].…”
Section: Tnf-αmentioning
confidence: 93%
“…Movements such as jumping, shooting, and intense body contact are also performed. In this very high-intensity sport the total distance traveled during a match can be as much as 4500-7000 m, heart rates reach around 170 beats per minute (BPM), and muscle damage may be evident after a match (Tanaka et al, 2002;Marin et al, 2011). Thus, handball is a sport that requires high aerobic and anaerobic abilities (Tanaka et al, 1997;Tanaka, 1999).…”
Section: Introductionmentioning
confidence: 99%